2021
DOI: 10.1002/ppsc.202000263
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐6 Loaded Polyelectrolyte Complex Nanoparticles Inducing Osteogenic Differentiation and Apoptosis of Malignant Plasma Cells for Local Treatment of Multiple Myeloma

Abstract: In the malignant plasma cell disease multiple myeloma (MM), bone lesions and resulting fractures caused by MM cell (MMC) accumulation represent a major cause of morbidity and mortality. Despite recent advantages in systemic treatment, residual MMCs remain, especially in bone lesions. Therefore an interfacial delivery system for local treatment of MM and induced bone disease based on polyelectrolyte complex nanoparticles (PEC NP) loaded with bone morphogenetic protein 6 (BMP‐6) inducing de‐novo bone formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…β-Gly supports bone formation by providing a phosphate source for hydroxyapatite formation and by promoting the phosphorylation of ERK1/2 . In terms of growth factors, Bone Morphogenic Proteins (BMPs), multifunctional growth factors within the transforming growth factor β (TGF-β) superfamily, are most frequently used due to their unique osteoinductive potential and crucial roles in skeletal development and maintenance. The canonical BMP signaling cascade initiates when BMPs associate with type I and type II BMP receptors to form a multimeric receptor ligand complex, followed by phosphorylation of BMP-specific Smads, including Smad 1, 5 and 8, to regulate the expression of the targeted genes, including Runx 2 and ALP. , Of the known BMP variants, BMP2, BMP6 and BMP9 have been shown to be the most potent inducers of osteoblast differentiation from MSCs. ,, Of these, although BMP2 has received FDA approval for clinical use, , BMP6 has been shown to be more potent (both in vitro and in vivo ). , Regardless, despite the remarkable potential of BMPs for bone regeneration and repair, broader clinical application is often hindered by their random folding, short half-life, high prices and immunogenicity. ,,, A viable alternative is a short peptide of the active domains of the protein capable of replicating the signaling cascades induced by the full length protein. Studies have shown that the biological activity of BMP-derived peptides is highly influenced by their carriers and that carriers designed to sustain the bioactivity and release of BMPp can lead to reduced effective dose sizes and reduced occurrence of side effects compared to full length proteins , …”
Section: Introductionmentioning
confidence: 99%
“…β-Gly supports bone formation by providing a phosphate source for hydroxyapatite formation and by promoting the phosphorylation of ERK1/2 . In terms of growth factors, Bone Morphogenic Proteins (BMPs), multifunctional growth factors within the transforming growth factor β (TGF-β) superfamily, are most frequently used due to their unique osteoinductive potential and crucial roles in skeletal development and maintenance. The canonical BMP signaling cascade initiates when BMPs associate with type I and type II BMP receptors to form a multimeric receptor ligand complex, followed by phosphorylation of BMP-specific Smads, including Smad 1, 5 and 8, to regulate the expression of the targeted genes, including Runx 2 and ALP. , Of the known BMP variants, BMP2, BMP6 and BMP9 have been shown to be the most potent inducers of osteoblast differentiation from MSCs. ,, Of these, although BMP2 has received FDA approval for clinical use, , BMP6 has been shown to be more potent (both in vitro and in vivo ). , Regardless, despite the remarkable potential of BMPs for bone regeneration and repair, broader clinical application is often hindered by their random folding, short half-life, high prices and immunogenicity. ,,, A viable alternative is a short peptide of the active domains of the protein capable of replicating the signaling cascades induced by the full length protein. Studies have shown that the biological activity of BMP-derived peptides is highly influenced by their carriers and that carriers designed to sustain the bioactivity and release of BMPp can lead to reduced effective dose sizes and reduced occurrence of side effects compared to full length proteins , …”
Section: Introductionmentioning
confidence: 99%
“…The canonical BMP signaling cascade initiates when BMPs associate with type I and type II BMP receptors to form a multimeric receptor ligand complex, followed by phosphorylation of BMP-specific Smads, including Smad 1, 5 and 8, to regulate the expression of the targeted genes, including Runx 2 and ALP [7c, 8] . Of the known BMP variants, BMP2, BMP6 and BMP9 have been shown to be the most potent inducers of osteoblast differentiation from MSCs [7e, 9] . Of these, although BMP2 has received FDA approval for clinical use [10] , BMP6 has been shown to be more potent (both in vitro and in vivo ) [11] .…”
Section: Introductionmentioning
confidence: 99%